KE ADAAN SARANA DAN PRASARANA PENDIDIKAN JASMANI DI S D SE UPTD KECAMATAN SEMARANG BARAT KOTA SEMARANG TAHUN 201 5 - Liska Sukiyandari (LP2M, 2018)
This study aims to determine the condition of facilities and infrastructure of PhysicalEducation in SD Se UPTD West Semarang District Semarang City Year 2015.This research is a descriptive research with survey research design. The subject ofthis research is teacher Penjas Se UPTD West Semarang District Semarang City.Data were collected through questionnaires, and interviews.From the results of research and analysis of data that has been described, then ingeneral sports facilities and infrastructure that includes the main or compulsivesports branch on the subject of Physical Education in Elementary Schools UPTDWest District can be knownfor gymnastics sports state facilities and infrastructure asa whole in conditions